Implications of Heterogeneity of Epithelial-Mesenchymal States in Acromegaly Therapeutic Pharmacologic Response - Joan Gil; Montserrat Marques-Pamies; Elena Valassi; Araceli García-Martínez; Guillermo Serra; Cristina Hostalot; Carmen Fajardo-Montañana; Cristina Carrato; Ignacio Bernabeu; Mónica Marazuela; Helena Rodríguez-Lloveras; Rosa Cámara; et al. (Biomedicines, 2022)
Acromegaly is caused by excess growth hormone (GH) produced by a pituitary tumor. First-generation somatostatin receptor ligands (SRLs) are the first-line treatment. Several studies have linked E-cadherin loss and epithelial-mesenchymal transition (EMT) with resistance to SRLs. Our aim was to study EMT and its relationship with SRLs resistance in GH-producing tumors. We analyzed the expression of EMT-related genes by RT-qPCR in 57 tumors. The postsurgical response to SRLs was categorized as complete response, partial response, or nonresponse if IGF-1 was normal, had decreased more than 30% without normalization, or neither of those, respectively. Most tumors showed a hybrid and variable EMT expression profile not specifically associated with SRL response instead of a defined epithelial or mesenchymal phenotype. However, high SNAI1 expression was related to invasive and SRL-nonresponsive tumors. RORC was overexpressed in tumors treated with SRLs before surgery, and this increased expression was more prominent in those cases that normalized postsurgical IGF-1 levels under SRL treatment. In conclusion, GH-producing tumors showed a heterogeneous expression pattern of EMT-related genes that would partly explain the heterogeneous response to SRLs. SNAI1 and RORC may be useful to predict response to SRLs and help medical treatment decision making.